THE ROLE OF ORAL ART IN THE DEVELOPMENT OF THE SPIRITUAL OUTLOOK OF THE YOUNG GENERATION (World Bulletin of Social Sciences, 2023)
In this article, the role and importance of examples of Uzbek folk art, especially the epic art in the further development of our national spiritual values, is highlighted, analyzed and appropriate conclusions are given.